MALUNGUNJEI: KOREOGRAFI TERINSPIRASI DARI GERAK TRADISI TARI BATAK SIMALUNGUN - Desy Wulan Pita Sari Damanik (Pixel :Jurnal Ilmiah Komputer Grafis, 2024)
The dance work entitled Malungunjei’s is a new work that develops the mangunjei movement motif in one of the Manduda dance motif movements. Malungunje’si comes from one of the names of the Batak Simalungun dance motifs, namely mangunjei. Mangunjei is a movement of both hands crossed in front of the chest and both hands on the left and right sides by turning the palms of the hands. The theme of this dance work is non-literal, because the presentation of this dance work is a development or exploration of the essence of the Mangunjei motif by utilizing intensity, large volume, and wide space for movement. Malungunjei's work is a group choreography consisting of three female dancers and two male dancers, a total of five dancers who will be composed in a large group composition and a small group by paying attention to the arrangement of parts. The costumes in this choreography use hiou material and the choice of colors is more on red, black and white, all three are colors used in every Batak Simalungun traditional activity. The dance music is formatted in MIDI with patterns resulting from the development of the Batak Simalungun gonrang. This work uses the exploration method as an initial part in developing the creativity of the creation process, improvisation to find movements by chance or spontaneously, composition to arrange the movements that have been obtained, and periodic evaluation and correction of the process.